TAHAP PEMBERDAYAAN KAMPUNG WISATA BERBASIS POTENSI DAN KEARIFAN LOKAL - Siti Zunariyah; Akhmad Ramdhon; Argyo Demartoto (UNIVERSITAS SEBELAS MARET (UNS), 2021)
Tourism sector has grown to be the superior one with the fastest growth in the world and has been a locomotive of economic growth. Setabelan, Surakarta attempts to develop a culture and locality-based tourism village. This action research aims to analyze the process of empowering villagers conducted in participative manner by involving stakeholders with Friedman’s community empowerment theory. The result of research shows that community empowering process was conducted through the stage of producing citizens’ knowledge on village’s history, potency, need, and problem. The result of knowledge production was used as the data to design workshop to citizens through Focus Group Discussion (FGD) mechanism. A series of workshops have been implemented because people have interest in packaging the village’s cultural potency as tourist attraction. Citizens’ cultural potency was packaged in the forms of village profile book, village diary, documentary video, village sketch, Open Street Map (OSM) and infographic published through website and social media in order to be accessible broadly. Thus, empowering village through the potency owned in cultural context will provide knowledge, belief, understanding, and custom or habit or ethics guiding human behavior in living within its community. Keywords: Empowerment, Tourism Village, Culture and Locality AbstrakSektor pariwisata telah tumbuh menjadi sektor unggulan dengan pertumbuhan tersepat di dunia dan menjadi lokomotif pertumbuhan ekonomi. Setabelan, Surakarta berupaya mengembangkan kampung wisata berbasis budaya dan lokalitas. Action research ini bertujuan untuk menganalisa proses pemberdayaan warga kampung yang dilakukan secara partisipatif dan melibatkan para stakeholders dengan teori pemberdayaan masyarakat dari Friedman. Hasil penelitian menunjukkan bahwa proses pemberdayaan masyarakat dilakukan melalui tahap produksi pengetahuan warga tentang sejarah, potensi, kebutuhan dan problem kampung. Hasil produksi pengetahuan digunakan sebagai data untuk merancang workshop bagi warga melalui mekanisme Focus Group Discussion (FGD). Rangkaian workshop terlaksana karena masyarakat punya kepentingan untuk mengemas potensi budaya kampung sebagai daya tarik wisata. Potensi budaya warga dikemas dalam bentuk buku profil kampung, diary kampung, video dokumenter, sketsa kampung, peta Open Street Map (OSM) maupun infografis dipublikasikan melalui website dan media sosial agar dapat diakses secara luas. Dengan demikian memberdayakan kampung melalui potensi yang dimiliki dalam konteks budaya akan memberi bentuk pengetahuan, keyakinan, pemahaman serta adat kebiasaan atau etika yang menuntun perilaku manusia dalam kehidupan di dalam komunitasnyaKata kunci: Pemberdayaan, Kampung Wisata, Budaya dan Lokalitas